2008
DOI: 10.1084/jem.20071859
|View full text |Cite
|
Sign up to set email alerts
|

Breaking tolerance to the natural human liver autoantigen cytochrome P450 2D6 by virus infection

Abstract: Autoimmune liver diseases, such as autoimmune hepatitis (AIH) and primary biliary cirrhosis, often have severe consequences for the patient. Because of a lack of appropriate animal models, not much is known about their potential viral etiology. Infection by liver-tropic viruses is one possibility for the breakdown of self-tolerance. Therefore, we infected mice with adenovirus Ad5 expressing human cytochrome P450 2D6 (Ad-2D6). Ad-2D6–infected mice developed persistent autoimmune liver disease, apparent by cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 68 publications
7
172
2
1
Order By: Relevance
“…However, the complete absence of an AIH in C57BL/6 and FVB/N mice in their model is rather puzzling. We 2 and others 5 found that AIH can be triggered in both these mouse strains. This could be attributed to the duration of the observation period, which is critical in view of the fact that we observed the development of AIH as late as 8 months after adenoviral infection.…”
Section: Autoimmune Hepatitis Experimental Model Based On Adenoviral mentioning
confidence: 53%
“…However, the complete absence of an AIH in C57BL/6 and FVB/N mice in their model is rather puzzling. We 2 and others 5 found that AIH can be triggered in both these mouse strains. This could be attributed to the duration of the observation period, which is critical in view of the fact that we observed the development of AIH as late as 8 months after adenoviral infection.…”
Section: Autoimmune Hepatitis Experimental Model Based On Adenoviral mentioning
confidence: 53%
“…Others' models did not see any fibrosis 2,3 or unphysiological subcapsular fibrosis just after intraperitoneal virus injection. 4 Other researchers have also described the need for strong "danger signals" to break tolerance against liver antigens 3-5 ; however, we could show that the mere overexpression of the autoantigen is not sufficient to cause AIH. This is well in line with the experience of Lapierre et al employing a repeated prime boost protocol with DNA vaccination with a plasmid encoding for a secreted chimeric antigen of cytochrome P4502D6 (CYP2D6) and formiminotransferase cyclodeaminase (FTCD), with the addition interleukin (IL)-12 2 or expression with an adenovirus.…”
mentioning
confidence: 59%
“…However, we did not try CYP2D6 as an orthologous autoantigen. The amount of virus could be excluded as a variable, because we tried 1 3 10 9 to 1 3 10 10 plaque-forming units of our adenovirus, as reported by Holdener et al 4 As recently discussed, 7 we think that all the mentioned models are important and can be used to explain various aspects of AIH and hepatic immune tolerance. …”
mentioning
confidence: 99%
“…Certain infectious microbes and special drug metabolites, such as antibiotic minocycline, statins and anti-tumor necrosis factor (TNF) agents such as infliximab (IFX), could masquerade the section of self-antigen and consequently trigger the immune attack by molecular mimicry. 10 Cytochrome P450 2D6 (CYP2D6) amino acids (aa) 193-212, which is one of the autoantigens of AIH, 11 has homologies with hepatitis C virus (HCV) RNA-dependent DNA polymerase NS5 aa 2977-2996 and cytomegalovirus (CMV) alkaline exonuclease aa 121-140. And up to 10% of the patients infected with HCV may be seropositive for anti-liver-kidney micrisomal (LKM) antibody.…”
Section: Pathogenesismentioning
confidence: 99%